The Effect of Using Interactive Learning Videos to Improve Learning Outcomes in ICT Subjects in Computer Systems Material - Pasya, Ilham Widya; Trisiana, Anita; Pandu W, Yudhistiro (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
This study aims to determine the application of interactive learning videos to student learning outcomes in ICT learning on computer systemmaterial in class IX SMP N 18 Surakarta. the subject of this study refers to class IX H SMP N 18 Surakarta with a total of 31students and the feasibility of using interactive learning videos. This research uses the Classroom Action Research ("CAR") methodconsisting of several cycles, each cycle consists of four steps, namely Planning, Implementation/Action, Observation, and Reflection. Thisresearch learning media with interactive learning video media. Data analysis uses those obtained from the results of classroom learningresearch with pretest and posttest instruments. The results showed that the learning outcomes of students in cycle I average value of 56 witha percentage of student success of 48.3% increased in cycle II with an average value of 58 with a percentage of student success of 58% thenin cycle III increased with an average value of 70 with a percentage of success of 70.9%. The results showed that there was an increase inthe learning outcomes of students in class IX H SMP N 18 Surakarta by 22.6%. The response of students to the video interactive learningmaterial was very enthusiastic and very good. This research contributes to learning methods for teachers so that learning becomes moreinteresting and can improve learning outcomes.Keywords: Interactive Learning Video, Learning Outcomes, Computer Systems